Developing motivation through an ICT cooperation project plan in English between Spanish and German students - Rubio, Antonio Daniel Juan (Universitas Syiah Kuala, 2024)
This case study aims to research the connection between motivation and real-life experiences in the use of the English language through an ICT cooperation project plan between two centres. Introducing Information and Communication Technologies (ICTs) by means of videoconferences and the Edmodo network, we connect teenagers from different countries who share hobbies and interests. The goal is that students from Spanish 3rd-grade compulsory secondary education or their equivalent 9th-grade German peers use English as a lingua franca to achieve their objectives. This also helps students to acquire a foreign language (English) in a motivating and communicative environment and to develop competencies that are usually relegated to the background in standard English classes. In total, 104 teenagers participated in this study, in which they had to write letters, record a video, and participate in three videoconferences. The research started with an online meeting between the two teams of teachers from both centres in which the general guidelines were set up. The research instruments that the students had to carry out during the project were pictures and letters, videoconferences, and finally a profile on an educational social network. The results show how this cooperation project motivated them to the point that they could end their school year with a better grade than they had before starting the project as they shared interests in the use of English to maintain cooperation with their peers.